Procedure for Handling 4-H Accounts: Establishing and Maintaining a County 4-H Foundation - Marilyn N. Norman; Joy C. Jordan (EDIS)
Revised! 4H5.6, a 2-page factsheet by Marilyn N. Norman and Joy C. Jordan, explains how to establish and maintain a County 4-F Foundation, listing specific tasks and agent responsibilities. Published by the UF Department of Family, Youth and Community Sciences, February 2007. Revised October 2007.